Commitment of Part-Time Students in Germany: An Empirical Analysis - Busch, Christoph W. (Journal of Applied Business Research, 2019)
The following empirical research investigated the difference of several form of commitment of part time students to their employer. Therefore, this study based on the three component model of Allen & Meyer (1990). Most of the previous empirical researches investigated the commitment of employees within an organization. The measurement of commitment of part time students to their employer is largely unexplored and build the research gap of the following empirical research. The objectives of the work are to present the previous scientific findings of the three components model of Allen & Meyer and to answer the question if and what extent the commitment of part time students in Germany changed during their study time.To test possible differences of commitment, the questionnaire with 24 items was used. 231 part-time students participated in the survey. In addition to the statistical basics, the differences of commitment were found by using a two sample t-test. A key finding of this research is that students at the end of their study time have a lower commitment to their employer as students at the begin of their study time.
Keywords: business; research; Commitment; Three Component Model; Part-Time Students